Quantitative evaluation of systems : 16th International Conference, QEST 2019, Glasgow, UK, September 10-12, 2019, proceedings /: 16th International Conference, QEST 2019, Glasgow, UK, September 10-12, 2019, proceedings. ([2019]) - Unknown
No abstract available